PENGARUH PENTING PELAJARAN AKUNTANSI BAGI ANAK SEKOLAH - Sinaga, Joice Margareth; Salim, Susanto (Jurnal Serina Abdimas, 2024)
In carrying out teaching activities at SMA 95 JAKARTA BARAT,during teaching activities the aim is to expand soft skills and hard skills in the world of accounting. As a writer,carrying out duties in the Education Unit, I gained a lot of experience that had never been done before. This experience provides the writer with the opportunity to continue to develop and learn better. The author wa given the opportunity to teach directly with students to teach material about accounting from general journals to service company reports. The aim of presenting this material is to provide broad knowledge to students regarding acoounting and to provide guidance to students about the world of collage.